Metal complexes of (LH2) ligand: 8,9-bis(hydroxyimino)-4,7,10,13-tetraaza-1,2,15,16-O-dicyclopentylidenehexadecane. Crystal structure, electrical and optical properties - Aydogdu, Y; Yakuphanoğlu, Fahrettin; Aydogdu, A; Saydam, S; Sekerci, M; Boydag, FS (Elsevier Science Sa, 2001)
Molecular semiconducting complexes constitute one of the most fascinating, recent research topics, deeply involving both chemists and solid states physicists. Considerable interest has been shown in the synthesis and study of molecular complexes which may behave like semiconducting materials or at least show high conductivities. In this study, structural, electrical and thermal conductivity and optical properties of some inorganic complexes were investigated. From the XRD data, the unit cells of the samples were found as L-Cu is amorphous and L-Ni, L-Co are orthorhombic. L-Cn, L-Ni and L-Co have n-type of electrical conductivity. Electrical and optical band gaps of the complexes were found to be 1.46-1.36, 2.68-2.71 and 1.40-1.32 eV, respectively. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: complex; transition metals; inorganic semiconductor; activation energy; XRD